Youth gambling from the perspective of high-school counsellors - Mandić, Sabina (Array, 2020)
Gambling is a relatively new form of risk behaviour in our area. Modern Croatian and foreign scientific studies suggest that there is a considerable prevalence of problem gambling among highschool students. The aim of this paper is to explore how highschool counsellors perceive youth gambling. In addition to other tasks, they are responsible for detecting risk behaviour among youths and ensuring prevention and early intervention. This research was conducted among 120 counsellors from 18 Croatian counties. In general, the results show that they encounter issues surrounding youth gambling relatively rarely and they underestimate the prevalence of this risk behaviour, despite being aware of the fact that gambling products are easily accessible to youths. At the same time, counsellors do not perceive themselves sufficiently competent to provide adequate interventions in this field and they are not familiar enough with the developed training and interventions in Croatia. The results are interpreted in terms of their practical implications and with the aim of ensuring necessary professional knowledge and skills.